The role of bacterial agents in the structure of deterioration of uteroplacental perfusion - V A Kaptilnyy; E V Yekimova; I V Kuznetsova; Yu B Uspenskaya (IP Berlin A.V., 2015)
Objective: to make analysis of isolated deterioration of blood flow in the pool of uterine arteries in low-risk pregnancy after 18-week gestation, to detect connection of blood flow deterioration with infection processes of different location in the organism of pregnant women.Methods. Doppler screening research was made as well as analysis of spectrograms of uteroplacental and fetal blood flow of 357 pregnant women. Results. Low-risk pregnancy was accompanied by high frequency of hyperdynamic deterioration in the system of "mother-placenta-fetus" (14%), most frequently was detected the reduction of perfusion data of uteroplacental blood flow (67.9%) with almost absolute dominance (prevalence) of one-sided deterioration; high correlation dependence was revealed between reduction of uteroplacental blood flow and existence of extragenital chronic infection foci (71.4%); asymptomatic bacteriuria and infection-and-inflammatory disease of laryngological organs; causal treatment improved hemodynamic rates, with idiopathic forms of uteroplacental perfusion deterioration, pathogenic treatment is recommended, dipiridamol - 75 mg daily (1/3 three times a day) is a chosen medicine.Conclusion. Isolated one-sided deterioration of uteroplacental blood flow during low-risk pregnancy may be considered as the mark of chronic infection foci in the body of a pregnant woman; well-timed diagnostics and causal treatment allow to avoid progressive deterioration of hemodynamic rates.